Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1002/(sici)1097-0231(20000430)14:8<696::aid-rcm930>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Error-systematics of determining elemental isotopic abundance ratios by the molecular ion beam method: a case study for the simultaneous isotopic analysis of lithium and boron as Li2BO2+

Abstract: The simultaneous isotopic analysis of lithium and boron by the Li2BO2+ ion beam method involves measurements of two different molecular abundance ratios (say, Rj+/-delta(j) and Rk+/-delta(k)), and subsequently extensive calculations to arrive at the analyte isotopic ratios (say, L and Y). It is not presently known how the measurement errors (delta(j) and delta(k)) are transformed into the errors of analysis (deltaL and deltaY). This work addresses this question from fundamental considerations. In the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(43 citation statements)
references
References 22 publications
(49 reference statements)
2
41
0
Order By: Relevance
“…either or both of δ Y and δ Z will be non‐zero). Moreover, as already demonstrated in the cases of some other examples of MIBM analysis,34,, 37 the errors of isotopic analysis (δ Y and δ Z ) are never expected to be the same as the experimental errors (δ j and δ k ). That is to say that, although it is always the experimental errors (either or both of δ j and δ k as non‐zero) which and only which can cause the results of analysis to be imperfect (either or both of δ Y and δ Z to have non‐zero values), the magnitudes of δ Y and δ Z will be controlled also by the data processing involved in analysis 34,.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…either or both of δ Y and δ Z will be non‐zero). Moreover, as already demonstrated in the cases of some other examples of MIBM analysis,34,, 37 the errors of isotopic analysis (δ Y and δ Z ) are never expected to be the same as the experimental errors (δ j and δ k ). That is to say that, although it is always the experimental errors (either or both of δ j and δ k as non‐zero) which and only which can cause the results of analysis to be imperfect (either or both of δ Y and δ Z to have non‐zero values), the magnitudes of δ Y and δ Z will be controlled also by the data processing involved in analysis 34,.…”
mentioning
confidence: 86%
“…Then, it can be shown that, for any given experimental errors (δ j and δ k ), the errors of analysis (errors of solutions δ Y and δ Z ) take the following forms:34 …”
Section: Principlesmentioning
confidence: 99%
See 3 more Smart Citations